2017
DOI: 10.1080/14767058.2017.1337740
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes following a trial of labor after Caesarean delivery: a population-based study

Abstract: Neonatal morbidity appears slightly increased among women with a TOLAC. However, morbidity and mortality are considerably increased in cases of uterine rupture. Appropriate selection and counseling of women for TOLAC should be undertaken as to minimize uterine rupture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Our study also adds to the limited evidence [16] about other measures of adverse perinatal outcome. Our findings are consistent with two large population-based studies conducted in the US [54,55] and several small non-population-based studies [36,37,56] that have reported an increased risk of various measures of neonatal morbidity or composite adverse neonatal outcome with planned VBAC compared to ERCS.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also adds to the limited evidence [16] about other measures of adverse perinatal outcome. Our findings are consistent with two large population-based studies conducted in the US [54,55] and several small non-population-based studies [36,37,56] that have reported an increased risk of various measures of neonatal morbidity or composite adverse neonatal outcome with planned VBAC compared to ERCS.…”
Section: Discussionsupporting
confidence: 92%
“…Since the AHRQ review ( 20 ) a total of 12 studies ( 33 , 40 , 42 , 46 , 50 , 51 , 59 , 64 , 65 , 70 , 72 , 77 ) (eight population-based) have reported on some form of neonatal respiratory intervention/morbidity. Two of the studies ( 42 , 72 ) did not confine their study population to term infants, although one ( 42 ) did conduct a sub-group analysis on “low-risk” women which excluded those who gave birth preterm.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies ( 42 , 72 ) did not confine their study population to term infants, although one ( 42 ) did conduct a sub-group analysis on “low-risk” women which excluded those who gave birth preterm. Eight of the studies ( 33 , 42 , 50 , 59 , 64 , 70 , 72 , 77 ) investigated the need for some form of ventilation, reporting absolute risks ranging from 0.08 to 2.54% for planned VBAC and 0.16–2.29% for ERCS. Four of these studies ( 42 , 59 , 64 , 70 ) found ∼1.1–1.2-fold increased risk of this outcome for planned VBAC compared to ERCS, although for one of the studies ( 42 ) the increased risk was only apparent among women considered to be “low-risk” and for another of the studies ( 57 ) no significant difference was found when ventilation > 6 h was considered.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding respiratory outcomes, Lehmann, Yang, and Kok [10,13,19] demonstrated higher rates of infant respiratory distress syndrome (IRDS) in the ERCD group. Litwin [20] described a higher need for assisted ventilation in ERCD neonates, while Studsgaard [14] reported higher neonatal depression (defined in the paper as Apgar score 5 min after birth < 7 and/or pH < 7 in vessels of the umbilical cord) in the VBAC cohort.…”
Section: Discussionmentioning
confidence: 96%
“…Only a few studies have examined the outcomes in women whose characteristics are only one prior cesarean and no prior vaginal deliveries [13,17,18]. Many studies have had more liberal inclusion criteria and included women that have had one caesarean section, but also a varying number of previous vaginal deliveries [1,6,9,11,12,14,[19][20][21]. We referred to both study types for comparison.…”
Section: Discussionmentioning
confidence: 99%